Principles of curriculum development to improve the quality of learning with Kurikulum Merdeka - Nina Nuraini; Levina Syafin Tejasukmana; Fauzan Yahtadi; Mega Tri Nadya (Universitas Pendidikan Indonesia, 2023)
The curriculum is a reference for education components in carrying out learning. The curriculum must constantly be updated to suit the needs of students from time to time. Curriculum development is essential so learning can follow applicable norms and laws and achieve educational goals, as stated in Law No. 20 of 2003. Until now, the Merdeka curriculum has become a new product of the curriculum development process. This study aims to determine the principles applied to create a curriculum, to know the directions in the Merdeka curriculum, and how the Merdeka Curriculum is developed. This research is descriptive qualitative, where the collection is carried out using the literature study method. Data comes from various literature related to curriculum development. This study describes its findings that the five principles of curriculum development and the characteristics of the independent curriculum are very diverse. The independent curriculum is an innovation that focuses on developing students' competencies to be helpful in society. The Independent Curriculum needs to focus on remote areas of Indonesia to equalize the quality of education throughout the country.